ITDC Sebagai Stimulan Pertumbuhan Sektor Perhotelan di Bali - Riyanti, Anti; Afifah, Azmi Noer; Jatnika, Aldi Yusna; Fitriana, Liani Yanti; Revano, Mochamad Zidane; Wijaya, Rangga; Maria Caacbay, Rodolfo III Sta.; Syaputra, Ryan Hadi; Azizis, Auliya Rajwa; Novitasari, Ria (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2025)
This study aims to analyze the role of PT Indonesian Tourism Development (Persero) or Injourney Tourism Development Corporation (ITDC) in encouraging the growth of the hospitality sector in Bali. through descriptive qualitative methods, this study focuses on analyzing the development of the hospitality sector in Bali before and after the presence of ITDC. vOne of the roles of ITDC which aims to improve the quality of tourism also encourages sector growth in the field of hospitality as accommodation that combines the 5A concept in tourism (Attractions, Accessibility, Amenity, Accommodation and Activities). So that there is a rapid increase in the number and capacity of star hotels, an increase in occupancy rates, as well as the entry of large amounts of foreign direct investment into the hospitality sector which is a driver of hospitality sector growth. The results show that ITDC has had a very significant impact on the growth of the hospitality sector in Bali. This research highlights the importance of the role of SOEs in encouraging the development of the tourism sector and making a real contribution to regional economic growth.